Pengembangan Buku Saku Intensifikasi Bahasa Arab di IAIN METRO dengan Menggunakan Model ADDIE - Nawang Wulandari (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2018)
This study explains the steps of developing a teaching material product in the form of an Arabic Pocket Book which is fun for beginners. The development model used in this study is the development of ADDIE models. Needs Analysis until the evaluation is carried out as a reference for development. Validation of Material Experts, Media Experts and Learning Practitioners is used to determine the feasibility of the Pocket Book developed. Based on the results of the analysis using Analysis Variant (ANOVA), the data obtained shows that the mean in the class taught using the developed Pocket Book is greater than the Mean in the class taught using pre-existing books, namely 35.64 and 29.76, so it can concluded that the use of the Pocket Book gives a better influence.